Stealing lives : the globalization of baseball and the tragic story of Alexis Quiroz - Marcano Guevara, Arturo J., 1968- (Indiana University Press, 2002)
While some Latin American superstars have overcome a history of discrimination to strike gold in baseball's big leagues, there are thousands more who never make it to 'The Show'. Stealing Lives focuses on the plight of one Venezuelan teenager and documents the abuses that take place as baseball becomes a globalized business. The authors reveal that in their efforts to secure cheap labor, Major League teams often violate basic human rights.